Preliminary Characterization of Chromium (VI) Solution Adsorption with Mytella charruana in Semi-Artificial Environments (2020)
The bivalve specie Mytella charruana has shown great potential as a bioindicator in natural waters and a biofilter for the adsorption of metals, such as Cr(VI). This species has been found in important densities in Cartagena de Indias Bay, where high concentrations of Cr(VI) have also been reported. Thus, the purpose of this paper is to study the potential of the bivalve specie Mytella charruana, grown in Cr(VI) rich media, as a bio-adsorption treatment for Cr(VI) removal in aquatic environments such as mangrove ecosystems. For the experimental setup the bivalves collected from the mangrove roots were distributed into 5 L glass containers filled with unfiltered water from the media, and additional Cr(VI) solutions to reach 20, 30 and 50 μg/L concentrations. The containers, prepared by triplicate and with 3 control tanks, were aerated for 4 days and samples were daily taken to follow the pH, conductivity, total dissolved solids, and Cr(VI) concentration in both water and biomass. The bivalve species demonstrated biological activity through the presence of feces and pseudofeces settled in the tanks, the reduction of Cr(VI) concentration in the water phase, with and efficiency that improved with the initial concentration, and the survivability of the individuals. The bivalves acted as biofilters for the removal of Cr(VI) in the media, and, although they are not accumulating the contaminant in their organisms but eliminating it through their feces and pseudofeces. © 2020, Springer Nature Switzerland AG.